Analisis Komparasi Produksi Bawang Merah Organik Dan Anorganik di Kecamatan Rejoso Kabupaten Nganjuk - Khoirunnisa, Tria Alfiatul; Mazwan, M. Zul (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2025)
Indonesia places shallots as one of the main agricultural commodities with high selling value. Among the various shallot producing regions in Indonesia, Nganjuk district is known as one of the largest producing areas and production centers for shallot commodities in Indonesia. Organic and inorganic shallot production is the focus of attention of farmers and agricultural actors today. The research objectives are (1) to analyze the various factors that contribute to shallot production, both inorganic and organic cultivation (2) to analyze the average difference in shallot production before and after the implementation of organic farming. The research method used is to conduct a quantitative approach technique to 20 respondents who apply organic, semi-organic as well as inorganic farming and 10 respondents who apply inorganic farming only. Data collection methods were carried out by observation, interviews and literature studies. The results revealed that production factors contribute to shallot yield. Factors that affect shallot yield are seed variables and dummy variables, which means the value is smaller than 0.05. The results of the analysis show that the variables of land area, fertilizer, pesticides, and labor do not have a real influence in determining shallot yield. Research on the comparison of average shallot production shows a significant difference between before and after the implementation of organic farming. To minimize the risk, steps are needed to provide support in the form of providing counseling and long-term assistance related to land to shallot farmers. Another step is the need for economic incentives for farmers who are willing to switch to organic farming, due to the transition period that has the potential to reduce productivity